Energy efficiency in Hungary and abroad - Török, Imre (Acta Agraria Debreceniensis, 2015)
Nowadays decentralized energy supply and the energy security are becoming more involved. We should increase the share of renewable in the energy mix, addition to improve the energy efficiency. Hungary is not an abundance of fossil resources it is particularly important in the materials and energy-saving technologies, waste recovery, increasing the share of environmental energy. Our country has outstanding opportunities many areas for example, solar energy, geothermal energy, so we need to devote more attention to renewables in the future.